The purloined puzzle [large type] - Hall, Parnell (Hall, Parnell. Puzzle Lady mystery., 2018)
When 16-year-old Peggy Dawson approaches Cora with a crossword puzzle that the girl thinks is important to solve, Cora foists her off on Harvey Beerbaum, a crossword expert. After the puzzle disappears, Harvey refers Peggy to police chief Dale Harper. Naturally, the puzzle, when found, connects to a murder-that of stabbing victim Fred Winkler-as does a bloody knife found by Peggy's brother, Johnny, in his room. The police settle on Johnny as a suspect in Winkler's death, but then find an even better one: Cora's ex-husband, Melvin Crabtree, whose planned tell-all book, Confessions of a Trophy Husband: My Life with the Puzzle Lady, threatens Cora's secret-that she's the public face for the crossword puzzles created by her niece Sherry Grant. A barrage of insults, put-downs, confusions, and double entendres will keep fans of light humorous mysteries happily turning the pages.